Integrasi Keunggulan Pesantren Salaf dan Khalaf pada Pondok Pesantren Al-Ansor Padangsidimpuan - Suheri Sahputra Rangkuti (Madaniyah, 2018)
Islamic boarding schools are among the educational nomenclature in this country. Even long before Indonesian independence, pesantren had first set foot and developed their wings to act to encourage and move for the independence of the Indonesian people. Over time, the pesantren which initially focused on the ukhrawi science gave birth to a new color, namely, pesantren which received the general education curriculum and took the form of a variety of pesantren termed Khalaf and who were still focused on the ukhrawi sciences called Salaf. It is very interesting if the characteristics and advantages of these two messages are combined. This article shows how the performance of the kiai and the philosophical values that inspired him in carrying out his managerial merge the two models. At the very least, this article is present to fill the empty space about the study of boarding school management.